2017
DOI: 10.1002/slct.201700333
|View full text |Cite
|
Sign up to set email alerts
|

Alleviation of Hepatotoxicity of Arecoline (Areca Alkaloid) by a Synthetic Receptor

Abstract: Arecoline, as one of the major biologically active compounds extracted from Areca nut, has shown profound links to hepatotoxicity. In this study, the inclusion of arecoline hydrobromide (AH) in a synthetic receptor, cucurbit[7]uril (CB[7]), was demonstrated by 1H NMR spectroscopic titration, isothermal titration calorimetry (ITC), electrospray ionization mass spectrometry (ESI‐MS), and density functional theory (DFT) molecular modeling. The results showed that AH formed 1:1 host‐guest complexes with CB[7], wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…51 Most recently, our research group demonstrated that, upon encapsulation of the natural, neurologically active compound arecoline hydrobromide (AH) in the cavity of CB [7], the inherent hepatotoxicity of AH was alleviated up to fourfold, when compared with that of the free AH, in the healthy human liver cell line L02. 54 Similarly, we also discovered that the in vitro hepatotoxicity of an anticancer candidate, NC, was also reduced upon complexation with CB [7], with the IC 50 value increased from 3.48 ± 0.49 M (free NC) to 6.87 ± 0.80 M (CB[7]-NC complex). 49 In another recent study, we showed that CB [7] reduced the inherent cardiotoxicity of the antituberculosis drug CFZ with an in vivo zebrafish model ( Fig.…”
Section: Effect On the Toxicity Of Complexed Drugsmentioning
confidence: 91%
See 1 more Smart Citation
“…51 Most recently, our research group demonstrated that, upon encapsulation of the natural, neurologically active compound arecoline hydrobromide (AH) in the cavity of CB [7], the inherent hepatotoxicity of AH was alleviated up to fourfold, when compared with that of the free AH, in the healthy human liver cell line L02. 54 Similarly, we also discovered that the in vitro hepatotoxicity of an anticancer candidate, NC, was also reduced upon complexation with CB [7], with the IC 50 value increased from 3.48 ± 0.49 M (free NC) to 6.87 ± 0.80 M (CB[7]-NC complex). 49 In another recent study, we showed that CB [7] reduced the inherent cardiotoxicity of the antituberculosis drug CFZ with an in vivo zebrafish model ( Fig.…”
Section: Effect On the Toxicity Of Complexed Drugsmentioning
confidence: 91%
“…In our recent studies, we also demonstrated that CB[7]–CPT exhibited lowered in vitro cytotoxicity (IC 50 = 3.562 ± 0.252 μM) to healthy liver cell L02 cells than free CPT (IC 50 = 0.562 ± 0.417 μM) after 24 h of incubation, and, more importantly, the complex also exhibited much lower nonspecific toxicities on wild‐type zebrafish in vivo when compared with CPT alone . Most recently, our research group demonstrated that, upon encapsulation of the natural, neurologically active compound arecoline hydrobromide (AH) in the cavity of CB[7], the inherent hepatotoxicity of AH was alleviated up to fourfold, when compared with that of the free AH, in the healthy human liver cell line L02 . Similarly, we also discovered that the in vitro hepatotoxicity of an anticancer candidate, NC, was also reduced upon complexation with CB[7], with the IC 50 value increased from 3.48 ± 0.49 μM (free NC) to 6.87 ± 0.80 μM (CB[7]–NC complex) .…”
Section: Effect On the Toxicity Of Complexed Drugsmentioning
confidence: 99%
“…For instance, arecoline (AH, Figure 1 B) is an active compound extracted from Areca nut that has been studied for the treatment of several neurological disorders, but also relatively to the cardiovascular and digestive systems. However, AH can show severe hepatotoxic effects 66 so CB 7 was tested as a supramolecular antidote to minimize its hepatotoxicity. The association between AH and CB 7 was first studied and has shown formation of a 1:1 complex with a binding affinity K a of (1.21±0.12)×10 3 M -1 .…”
Section: Cucurbiturilsmentioning
confidence: 99%
“…The association between AH and CB 7 was first studied and has shown formation of a 1:1 complex with a binding affinity K a of (1.21±0.12)×10 3 M -1 . Subsequent work demonstrated a reduction of the hepatic toxicity of AH in vitro based on tests performed on L02 cell lines 66 . Nitidine chloride (NC, Figure 1 B) is a natural alkaloid extracted from the root of Zanthoxylum nitidum 67 and a promising drug candidate against cancer, but further studies were impeded by its hepatic toxicity.…”
Section: Cucurbiturilsmentioning
confidence: 99%